Increasing population employment and competitiveness through business development strategy in enterprises - Khudoynazarov Sar dor Safarovich (THE INNOVATION ECONOMY, 2026)
This article proposes the formation of an innovative system for Uzbekistan to take its position as a country that can compete in international markets with telecommunications services and goods using a business develop ment strategy. It is shown that in the current conditions, the demand for the quality of telecommunications services and goods and competitive relations are of decisive importance